(2 4/5 - 1 3/10) : 3 3/4 - 2/15
Daje naj​


Odpowiedź :

Odpowiedź:

( 2 i 4/5 - 1 i 3/10) : 3 i 3/4 - 2/15=( 2 i 8/10 - 1 i 3/10) : 3 i 3/4 - 2/15=

   =1 i 5/10 : 3 i 3/4 - 2/15= 15/10 : 15/4 - 2/15= 15/10 *4/15 - 2/15 ( skracamy 15

                  i 15 przez 15, oraz 10 i 4 przez 2)=1/5*2- 2/15= 2/5- 2/15=

            =  6/15- 2/15= 4/15

Szczegółowe wyjaśnienie:

Odpowiedź:

[tex](2\frac{4}{5}-1\frac{3}{10}):3\frac{3}{4}-\frac{2}{15}=(2\frac{8}{10}-1\frac{3}{10}):\frac{15}{4}-\frac{2}{15}=1\frac{5}{10}:\frac{15}{4}-\frac{2}{15}=1\frac{1}{2}\cdot\frac{4}{15}-\frac{2}{15}=\\\\=\frac{\not3^1}{\not2_{1}}\cdot\frac{\not4^2}{\not15_{5}}-\frac{2}{15}=\frac{2}{5}-\frac{2}{15}=\frac{6}{15}-\frac{2}{15}=\frac{4}{15}[/tex]